STUDENTS’ MOTIVATION IN CHOOSING A JOB (A Study of English Department Students’ of STKIP Siliwangi Bandung) - Sudiyono Sudiyono (Eltin Journal : Journal of English Language Teaching in Indonesia, 2016)
This research is aimed to know the motivation of students’ to choose a job. In this research the subjects of the research  are the students of English Department of STKIP Siliwangi Bandung, academic year 2013-2013.Besides motivation, this research also wants to deep and to describe what are the reasons of the respondents to choose each motivation.In this research the writer used a descriptive qualitative method, a research which is used in the case study, documents analysis, and corelation research. As the result of data process analysis showed, there are 18 students of 80 respondents chose  good working relationship as their choice to get a job. It means 22.5% of respondents chose ‘good working relationship’ as motivation of work. As the result of data process analysis showed, there are 18 students of 80 respondents chose  good working relationship as their choice to get a job. It means 22.5% of respondents chose ‘good working relationship’ as motivation of work. As the result of data process analysis showed, there are 15 students of 80 respondents chose  responsibility as their choice to get a job. It means 18.75% of respondents chose  ‘responsibility’ as motivation of work. Keywords: motivation, remuneration, working relationship,  responsibility.